O primeiro dia europeu de Portugal : a televisão como legitimadora de decisões políticas - Machado, Gisela (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The text analyses the treatment given by RTP to the signature of the Treaty of Accession to the EEC (12/06/1985), the second biggest mediatic national event which had taken place until then after 1974. One suggests that the event is treated by RTP not only in a purely informative register, but also as a ceremonial mediatic event or teleceremony, an event-monument constructed by the television technicians to perpetuate the instant in which Portugal became a member of the EEC.